Investigation of suspected Mpox cases and differentiation from varicella in Cinkansé, Burkina Faso, August 2024 - Morou Nikiema; Aboubacar Sidiki Ouedraogo; Yacouba Zampalegre; Kalaga Assané; Denis Yelbeogo; Bérenger Yewayan Larba Kabore; Mady Saidou Bagaya; Dahourou Sou; Wendpanga Edith Roukietou Ouedraogo; Issa Guire (Journal of Interventional Epidemiology and Public Health)
Introduction: Monkeypox (Mpox) is an emerging viral zoonosis. On 16 August 2024, the Cinkansé border medical centre reported two (02) suspected cases of Mpox. Faced with this situation, an investigation was carried out around these cases from 16 to 20 August 2024 to confirm the cases and implement prevention and control measures.